The Date and Nature of Sphujidhvaja’s Yavanajātaka Reconsidered in the Light of Some Newly Discovered Materials - Mak, Bill M. (History of Science in South Asia)

(untitled) (University of Alberta Library, 2013)
This paper examines a number of crucial verses from the last chapter of Sphujidhvaja’s Yavanajātaka, a text that was widely believed to be the earliest Greek astral text translated into Sanskrit. In the light of some new materials, including a hitherto unreported Nepalese paper manuscript from the collection of the NepalGerman Manuscript Preservation Project (NGMPP), the date and nature of this important text are reconsidered.